ANALISIS FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO: Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2015 - Yuwono, Wahyu; Kurniawati, Indah (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2018)
The dividend payout ratio determines the amount of profit divided into cash dividends and retained earnings as a source of funding. This ratio shows the percentage of company earnings paid to the company's common shareholders in the form of cash dividends. This research was conducted at manufacturing companies listed on BEI. The technique of determining the sample in this study using purposive sampling method. The type of data used is secondary data derived from annual financial statements. Data collection techniques used are documentation techniques. Manufacturing companies listed on the Stock Exchange from 2012-2015 amounted to 143, while companies that fit the criteria in this study as many as 21 companies or 15%. Data analysis technique used multiple linear regression analysis. The result of hypothesis testing from this research shows that firm size and return on assets influence to dividend payout ratio while cash position, ownership, free cash flow, investment opportunity set does not affect dividend payout ratio.